Odpowiedź :
a) f (x)= x- 8
y>0
x-8>0
x>8
y<0
x-8<0
x<8
b) f (x)= -0.5x + 5.5
y<0
-0,5x+5,5<0
-0,5x<-5,5
x>11
y>0
-0,5x+5,5>0
-0,5x>-5,5
x<11
c) f (x)= ¾ x +½
y<0
¾ x +½ <0
¾ x <-0,5/0,75
x<0,66
x>0,66
y>0
x-8>0
x>8
y<0
x-8<0
x<8
b) f (x)= -0.5x + 5.5
y<0
-0,5x+5,5<0
-0,5x<-5,5
x>11
y>0
-0,5x+5,5>0
-0,5x>-5,5
x<11
c) f (x)= ¾ x +½
y<0
¾ x +½ <0
¾ x <-0,5/0,75
x<0,66
x>0,66
a) x-8>0
x>8
b)
-0,5x+5,5>0
5,5>0,5x /*2
11>x
c)
3/4x+1/2>0 /*4
3x+2>0
3x>-2
x>-2/3
Dla tych są dodatnie gdy zmienisz > na < będą ujemne :)
x>8
b)
-0,5x+5,5>0
5,5>0,5x /*2
11>x
c)
3/4x+1/2>0 /*4
3x+2>0
3x>-2
x>-2/3
Dla tych są dodatnie gdy zmienisz > na < będą ujemne :)